2022
DOI: 10.1161/strokeaha.121.038153
|View full text |Cite
|
Sign up to set email alerts
|

Fragility Index Meta-Analysis of Randomized Controlled Trials Shows Highly Robust Evidential Strength for Benefit of <3 Hour Intravenous Alteplase

Abstract: Background: Cumulative fragility index (FI) analysis enables quantification of the evidential strength of intravenous alteplase’s core indication—treatment of disabling acute ischemic stroke within 3 hours of onset. Methods: Meta-analyses were performed (study level) or identified (individual participant level) for freedom-from-disability (modified Rankin Scale [mRS] score 0–1, primary efficacy), functional independence (mRS score 0–2, secondary efficac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(21 citation statements)
references
References 26 publications
0
21
0
Order By: Relevance
“…However, the fragility index was calculated at 5 indicating a 'somewhat robust' result (Supplemental eFigure 25). 28 EVT-treated patients also had higher odds of achieving mRS 0-2 at 3 months compared with BMT-treated patients (OR: 2.91; 95% CI: 1.51-5.61; seven studies; I 2 = 62%; p for Cochran's Q = 0.02; p for subgroup differences = 0.10; Supplemental eFigure 26). This significant difference was further accentuated in sensitivity analysis (OR: 3.54; 95% CI: 1.97-6.39; Supplemental eFigure 27).…”
Section: Quantitative Analysesmentioning
confidence: 97%
See 1 more Smart Citation
“…However, the fragility index was calculated at 5 indicating a 'somewhat robust' result (Supplemental eFigure 25). 28 EVT-treated patients also had higher odds of achieving mRS 0-2 at 3 months compared with BMT-treated patients (OR: 2.91; 95% CI: 1.51-5.61; seven studies; I 2 = 62%; p for Cochran's Q = 0.02; p for subgroup differences = 0.10; Supplemental eFigure 26). This significant difference was further accentuated in sensitivity analysis (OR: 3.54; 95% CI: 1.97-6.39; Supplemental eFigure 27).…”
Section: Quantitative Analysesmentioning
confidence: 97%
“…The fragility index of this outcome was calculated at 10, suggesting a 'somewhat robust' result (Supplemental eFigure 28). 28 Regarding safety outcomes, sICH occurred more often in EVT-treated patients compared with BMT-treated patients (OR: 2.30; 95% CI: 1.18-4.48; six studies; I 2 = 45%; p for Cochran's Q = 0.11; p for subgroup differences = 0.68; Supplemental eFigure 29). The difference between the two treatment groups was attenuated and became non-significant in the sensitivity analysis (OR: 2.01; 95% CI: 0.97-4.16; Supplemental eFigure 30).…”
Section: Quantitative Analysesmentioning
confidence: 99%
“…AF detection was significantly more common in the PCM group compared to controls (RR: 3.85; 95% CI: 2.59–5.73; 7 studies; I 2 = 58%; p for Cochran Q = 0.03; Figure 3) and the overall effect was considered highly robust (FI = 73). 29 This association was also significant in the subgroup of RCTs investigating ICM versus conventional monitoring (RR: 3.86; 95% CI: 2.24–6.64; 4 studies; I 2 = 59%; p for Cochran Q = 0.06; Supplemental Figure 8). The sensitivity analysis including four studies with a follow-up duration of ⩾12 months confirmed the overall effect of the primary analysis (Supplemental Figure 9).…”
Section: Resultsmentioning
confidence: 88%
“…Publication bias across individual studies was assessed when more than four studies were included in the analysis of the outcomes of interest, using both funnel plot inspection and the Egger et al’s linear regression test, 26 and the equivalent z test for each pooled estimate with a two-tailed p value <0.05 was considered statistically significant. Furthermore, analysis of dichotomous outcomes allowed the calculation of the fragility index (FI), 27,28 which was assessed based on the classification by Mun et al 29 suggesting that a FI ⩽ 4 was indicative of a non-robust result; a 4 < FI ⩽ 12 corresponded to a somewhat robust result; a 12 < FI ⩽ 34 indicated a robust result; and, finally, a FI > 34 was suggestive of a highly robust result. It should be noted, though, that FI has been recently criticized and should be interpreted as an additional measure of robustness and in conjunction with the other available statistical summaries that have been also used in the current meta-analysis.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent study on the cumulative fragility index of studies on alteplase within the 3-hour window confirmed the evidence is highly robust. 13 The CADTH rapid review suggests "investigating whether there is a need to re-analyze data from other trials," but this has already been extensively done. An independent committee in 2004 8 and multiple other re-analyses of the NINDS trials all confirm the findings of benefit.…”
Section: Efficacy Of Alteplase Within 3 Hours Of Symptom Onsetmentioning
confidence: 99%